Aortic Dissection Complicated With Superior Mesenteric Artery Aneurysm - Hisato Takagi (Clinical Case Reports, 2025)
ABSTRACT A case of acute type B aortic dissection (intramural hematoma) complicated by superior mesenteric artery aneurysm is herein reported. It is suggested that the coexistence of aortic dissection and superior mesenteric artery aneurysm should be based upon the shared etiology.